Determination of Drying Induced Stresses in a Prismatic Bar - A. Rybicki (Engineering Transactions, 1993)
In the paper a solution of the two-dimensional problem of convective drying of porous – capillary material is presented. The considered phenomenon is described by a system of coupled differential equations proposed by KOWALSKI [7, 8]. The problem is solved with the use of the finite element method for spatial derivatives and of the three-point finite difference method for derivatives with respect to time. The obtained results with special emphasis on the stress distributions are shown diagrammatically.